"Expectations to Change" (E2C): A Participatory Method for Facilitating Stakeholder Engagement With Evaluation Findings. (June 2015) - Adams, Adrienne E.; Nnawulezi, Nkiru A.; Vandenberg, Lela
From a utilization-focused evaluation perspective, the success of an evaluation is rooted in the extent to which the evaluation was used by stakeholders. This paper details the "Expectations to Change" (E2C) process, an interactive, workshop-based method designed to engage primary users with their evaluation findings as a means of promoting evaluation use and building evaluation capacity. The process is uniquely suited for contexts in which the aim is to assess performance on a set of indicators by comparing actual performance to planned performance standards for the purpose of program improvement. The E2C process was originally developed for use in a participatory evaluation with a non-profit human service organization. Evidence from a one-year follow-up survey suggested that the method increased participants' conceptual, instrumental, and process use. The general utility of the E2C process is discussed.